PERBEDAAN SATURASI OKSIGEN PERIFER ANTARA PEMBERIAN TEKANAN SUCTION 150 DAN 110 mmhg - Oky Riyanto Wibowo; Umi Kalsum; Diah Setiani (Poltekkes Kemenkes Kalimantan Timur, 2021)
Abstract The suction action has side effects, which is susceptible decline in oxygen saturation (SpO 2), not only sucked mucus but also inhaled oxygen, the condition is called hypoxia and is very dangerous because it can cause brain cell death. This study aims to determine differences in peripheral oxygen saturation (SpO 2) between the suction giving 150 and 110 mmHg. This study is a quasi-experimental research, design using pre-test and post-test nonequivalent control group.The sample is divided into two groups each containing 9 respondents. Bivariate analysis performed three times by using Wilcoxon, idependent T-test, and Mann Whitney. Value pre test in group 1 and group 2 the mean values obtained in group 1 was 9.67 and in group 2 is 9.33, then the p value 0.866 <0.05 and value post-test in group 1 and group 2 the mean values obtained in Group 1 is 5.00 and in group 2 is 14.00 then p value 0.000 <0.05. In this study we can conclude that the intervention group 1 suction pressure of 150 mmHg greater influence in the decline of peripheral oxygen saturation, rather than intervention by the suction pressure of 110 mmHg. Keywords: ETT, Suction, Peripheral Oxygen Saturation.